2021
DOI: 10.1590/1980-549720210031
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and overweight: is there a relationship in adolescence?

Abstract: Objective: This study aimed to investigate the association between sleep duration and excess weight in Brazilian adolescents. Methods: This is a cross-sectional study conducted with 65,837 adolescents, aged 12 to 17 years, enrolled in the Study of Cardiovascular Risks in Adolescents (ERICA). Sleep duration was assessed by means of a questionnaire focusing on weekday and weekend hours of sleep. Nutritional status was assessed based on body mass index, and participants were classified according to age and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
3
0
2
Order By: Relevance
“…Therefore, the guidance was effective from this perspective. The current study, in conformity with others, 30,32,34,35 shows that sleep compensation during the weekends is a relevant factor and requires guidance to prevent adolescents from delaying sleep time on school days.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the guidance was effective from this perspective. The current study, in conformity with others, 30,32,34,35 shows that sleep compensation during the weekends is a relevant factor and requires guidance to prevent adolescents from delaying sleep time on school days.…”
Section: Discussionsupporting
confidence: 89%
“…This variable was controlled due to the possibility of influencing sleep parameters, such as the amount of sleep hours per day. 30,31 Adolescents should sleep between 8.5 and 10.5 hours a day to support their metabolism and other biological functions, which may be altered by sleep deprivation. 32 The students' Portuguese and mathematics marks were higher before the intervention, which may be related to the Table 3 Correlations regarding the use of technologies, insomnia and sleepiness pre-and postintervention through the STRICT, ISI, ans PDSS instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other studies have shown that lack of sleep duration could increase a person's risk of being overweight and obese 33 . Another study showed that adolescents with short sleep duration had a 1.1 times greater risk of being overweight than adolescents with long sleep duration (> 11 hours/day) 34 .…”
Section: Resultsmentioning
confidence: 89%
“…Para el presente estudio, la muestra analítica fue de n= 99 estudiantes, los cuales fueron seleccionados mediante un muestreo no probabilístico por conveniencia. Los criterios de inclusión fueron ser alumno inscrito durante el periodo 2023-1 en cualquiera de los ocho semestres, se excluyeron participantes con algún padecimiento neurodegenerativo y se eliminaron aquellos registros incompletos o con valores extremos en la cantidad de horas de sueño por noche (≤4 horas o ≥12 horas) (n= 5) (Corrêa, de Souza Borges, & Araújo de Oliveira, 2021).…”
Section: Muestra Y Muestreounclassified